Efficacy and tolerability of zuranolone in patients with depression: a meta-analysis of randomized controlled trials - Qiu, Youjia; Tao, Yuchen; Duan, Aojie; Wei, Xingzhou; Wang, Menghan; Xie, Minjia; Chen, Zhouqing; Shang, Jing; Wang, Zhong (Frontiers in Pharmacology, 2024)
Background: As a novel antidepressant drug, zuranolone has been initially applied in treating depression. This study investigated the efficacy and safety of its administration in patients with depression.The Embase, PubMed, and Cochrane library databases were searched for available studies up to Nov 1, 2023. The primary outcome was the change on day 15 depression severity scores compared to baseline. Secondary outcomes included remission and response rates on day 15. Safety outcomes included incidence of treatment-emergent adverse events (TEAEs) and individual AEs. Trial sequence analysis (TSA) was used to evaluate the ideal samplesize.Results: Six studies with 1884 patients were included. Zuranolone offered significantly greater changes in day 15 depression severity scores (mean difference = 2.43, 95% confidence interval [CI]: 1.36 to 3.49, p < 0.00001) compared to placebo; this was also observed at other time points. Differences in response (relative risk [RR] = 1.33, 95% CI: 1.15 to 1.54, p < 0.0001) and remission (RR = 1.46, 95% CI: 1.15 to 1.85, p = 0.002) rates were also statistically significant. For safety outcomes, zuranolone group showed more incidence of TEAE than the placebo group (RR: 1.15, 95% CI: 1.06 to 1.25, p = 0.0005, I 2 = 0%). As for individual AEs, significant differences were observed in dizziness (RR = 2.17, 95% CI: 1.22 to 3.86, p = 0.008) and somnolence (RR = 2.43, 95% CI: 1.35 to 4.37, p =0.003. No significant difference was observed in other AEs. The result of TSA indicated that the cumulative curve crossed the conventional (Z= 1.96) boundary but not reach TSA boundary (RIS = 1910).Our findings suggest that zuranolone has a rapid short-term antidepressant effect during administration. Although more TEAEs were observed in zuranolone, most of them were slight and temporary. However, studies with larger sample sizes and longer follow-up are needed.